2018
DOI: 10.1074/jbc.ra118.002215
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct sites of client protein interaction with the chaperone cpSRP43

Abstract: Integral membrane proteins are prone to aggregation and misfolding in aqueous environments and therefore require binding by molecular chaperones during their biogenesis. Chloroplast signal recognition particle 43 (cpSRP43) is an ATP-independent chaperone required for the biogenesis of the most abundant class of membrane proteins, the light-harvesting chlorophyll a/b-binding proteins (LHCPs). Previous work has shown that cpSRP43 specifically recognizes an L18 loop sequence conserved among LHCP paralogs. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The conserved Tyrosine at position 204 in ANK3 of cpSRP43 recognizes the FDPLGL sequence in L18 (7,8,15,20,22). However, this interaction alone would not be adequate to guard the trans-membrane domains (TMDs) from aggregation (47). Investigation into how cpSRP43 can protect the TMDs of LHCP has only recently been communicated.…”
Section: Cpsrp43 Protects Hfgf1 and Lysozyme From Heat-induced Aggregmentioning
confidence: 99%
See 4 more Smart Citations
“…The conserved Tyrosine at position 204 in ANK3 of cpSRP43 recognizes the FDPLGL sequence in L18 (7,8,15,20,22). However, this interaction alone would not be adequate to guard the trans-membrane domains (TMDs) from aggregation (47). Investigation into how cpSRP43 can protect the TMDs of LHCP has only recently been communicated.…”
Section: Cpsrp43 Protects Hfgf1 and Lysozyme From Heat-induced Aggregmentioning
confidence: 99%
“…Investigation into how cpSRP43 can protect the TMDs of LHCP has only recently been communicated. Mapping of interaction sites between cpSRP43 and LHCb5 was done by alkylation efficiency of LHCb5 cysteine mutants using N-ethylmaleimide followed by sitespecific cross-linking and the results of this combination of experiments revealed that cpSRP43 makes contacts and protects all three TMDs of the LHCb5 substrate (47). In site-directed mutagenesis studies, residues were categorized into two classes being mutations which disrupted cpSRP43's chaperoning of LHCP but not the binding of L18 and mutations in which both were disrupted (47).…”
Section: Cpsrp43 Protects Hfgf1 and Lysozyme From Heat-induced Aggregmentioning
confidence: 99%
See 3 more Smart Citations